The newest composition techniques and contemporary music genealogy (Journal of Philosophy Culture and Political Science, 2021)
The article is devoted to the genealogy of contemporary music and the evolution of the newestcomposition techniques. Parallels are drawn between discoveries in science and changes in art. Thedescribed processes are based on the author’s personal experiences. Some world music centers werenoted where the modern style is being improved, the future of music is evolving and is being forged andworld premieres are held. In particular, Impuls (Graz, Austria), Accademia Santa Cecilia (Rome, Italy),Conservatorio Giuseppe Verdi di Milano (Italy), Conservatorio C.Pollini di Padova (Italy), where the authorhad numerous opportunities to discuss the latest composing techniques with the creators, poets andarchitects of new music. Existing methods and concepts of playing various musical instruments as well asnew techniques and their development are demonstrated and structurally analyzed in the context of theauthor’s music. Namely, the use of extended techniques is shown on the example of «Omaggio a IvanFedele» (Tribute to Ivan Fedele) for solo flute, the ability to comprehend the primary musical material ofa modern score is based on «Tears of Silence», concerto for piano and symphony orchestra. The functionsof «Campo armonico» (harmonic field) are viewed on the example of «Ombre del Vuoto» (Shadowsof the void) for 11 performers (flute, oboe, clarinet, bassoon, trumpet, triangle, gran cassa, tam-tam,vibraphone, piano, I and II violin, viola, cello). New methods of organizing time in music are shown onthe example of «Serenata di stelle invisibili» (Serenade of invisible stars) for 5 performers (flute, clarinet,alto saxophone, cello, piano). The article is about the correlation between composer’s and performingtechniques and the emergence of a new timbre-Textur musical space-time coordinate.Key words: contemporary music, avant-garde, sonoristics, microtones, multiphonics.